The effect of tofacitinib on function and quality of life indicators in patients with rheumatoid arthritis resistant to synthetic and biological disease-modifying antirheumatic drugs in real clinical practice: Results of a multicenter observational study - D. E. Karateev; D. E. Abdulganieva; A. R. Babaeva; A. A. Baranov; L. P. Evstigneeva; O. N. Ivanova; G. V. Lukina; E. L. Luchikhina; V. I. Mazurov; A. S. Misiyuk; O. V. Semagina; A. E. Sizikov; et al. (Современная ревматология)
Tofacitinib (TOFA), a representative of a new class of targeted synthetic disease-modifying antirheumatic drugs (s-DMARD), is a promising drug for treating rheumatoid arthritis (RA) and other immune inflammatory diseases.Objective: to evaluate the efficiency and safety of therapy with TOFA in combination with methotrexate (MTX) and other s-DMARDs in real clinical practice in patients with active RA and previous ineffective therapy.Patients and methods. A 6-month Russian multicenter study of function and quality of life enrolled 101 patients with resistant RA: 18 men and 83 women; mean age, 51.03±11.28 years; mean disease duration, 105.4±81.43 months; rheumatoid factor-positive individuals (89.1%); and anticyclic citrullinated peptide antibody-positive ones (74.7%). 93 (92,1%) of these patients completed a 24-week study. TOFA was used as both second-line drug (after failure of therapy with s-DMARD) (n=74) and as a third-line drug (after failure of therapy with s-DMARDs and biological agents (BAs) (n=74). The tools RAPID3, HAQ, and EQ-5D were used to determine disease outcomes from a patient's assessment.Results. All the three tools demonstrated significant positive changes at 3–6 months following therapy initiation. RAPID3 scores for the status of a patient achieving a low disease activity or remission coincided with the mean DAS28-ESR and SDAI scores in 60% and 68% of cases, respectively. The achievement rates of the minimally clinically significant improvement (ΔHAQ≥0.22) and functional remission (HAQ≤0.5) at 6 months of TOFA therapy were 79.6 and 30.1%, respectively. The mean change value in EQ-5D scores over 6 months was -0.162±0.21. There were no significant between the groups of patients who used TOFA as a second- or third-line agent in the majority of indicators, except EQ-5D scores at 6 months.Conclusions. The results of our multicenter study using considerable Russian material confirmed the pronounced positive effect of TOFA used as a second-line agent (after s-DMARD failure) and a third-line agent (after s-DMARD and BA failure) on patients' assessment of disease activity, functional ability in daily life, and quality of life.